Smart Campus Strategy in Islamic Higher Education: Enhancing Service Quality through IT Governance at IAIN Pontianak - Syarif; Ali Hasmy; Rosidah Rosidah; Segu Segu; Budiyono Budiyono (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2026)
The digital transformation imperative in higher education demands strategic approaches to enhance service quality. This study investigates the strategic management of smart campus information systems at IAIN Pontianak, examining how Islamic values are integrated into digital transformation. A convergent embedded mixed-method case study was employed, collecting qualitative data through interviews with 157 participants and document analysis, complemented by quantitative surveys. Findings reveal that strategic formulation through Rector Decrees No. 430/2021 and No. 500/2021 enabled systematic implementation of integrated systems (SIAKAD, e-Learning, e-Office), achieving efficiency gains of 79-88%, 88% reduction in data inconsistencies, and 84.1% user satisfaction (χ² = 24.37, p = 0.002). Strategic evaluation addressed 83% of the identified issues. However, challenges persisted: 23% faculty resistance, digital literacy gaps (staff over 45 required 3.4 vs 0.7 support requests; t = 4.82, p < 0.001), and technical disruptions. The study advances theory by: (1) extending strategic management with a digital capability-building dimension; (2) modifying Servqual, adding Digital Accessibility and System Reliability; and (3) developing an Itqan-Servqual Integrated Model operationalizing Islamic values (perfection, precision, clarity, thoroughness) into concrete quality dimensions with empirical evidence. The model positions Islamic values as core quality principles enhancing mainstream frameworks. The study demonstrates that strategic smart campus management significantly enhances service quality when supported by strong leadership and systematic evaluation, though challenges in digital literacy require differentiated interventions.